Analysis of Mathematical Problem-Solving Ability of Class XI Senior High School Students on Sequences and Series Materials - Resi Erni (Journal of Research on Mathematics Instruction (JRMI), 2021)
The objective of this study was to analyze the mathematical problem-solving abilities of class XI high school students in solving sequence and series questions. This research is a descriptive study that aims to describe the mathematical problem-solving ability of class XI students in solving problems of sequences and series. The population in this study were students of class XI SMA in the academic year 2020/2021. The sample was selected by purposive sampling obtained students XI MIPA 1 totaling 25 students. The data was obtained from the results of the mathematical problem-solving ability essay test on the material of sequences and series as many as 4 questions taken from the 2018 National Examination questions. The purpose of this study was to determine and analyze students' mathematical problem-solving abilities on the material of sequences and series. From the results of the study, it can be concluded that the mathematical problem-solving ability on indicators 1, 2, and 3 are categorized as medium and high. In accordance with the research method, students are categorized as having low mathematical problem-solving abilities if they obtain medium, high, and very high criteria. The percentage of indicator 1 is 68.75%, the percentage of indicator 2 is 55.75%, the percentage of indicator 3 is 62.2% while the percentage of indicator 4 is 34.75.